Poliovirus type 3: molecular cloning of the genome and nucleotide sequence of the region encoding the protease and polymerase proteins. - Cann, A J (1983)
Overlapping cDNA clones representing the entire genome of poliovirus type 3 have been prepared in E. coli by two separate methods. Cloning of RNA . cDNA hybrids produced a more comprehensive set of clones with generally larger cDNA inserts than cloning of double - stranded cDNA. A restriction map of the entire genome and the nucleotide sequence of 2003 bases from the 3' terminus, comprising the region encoding the protease and polymerase proteins, are presented.